Synthesis Gold Nanoparticles by Plasma Jet as Different Diameters of System - Adil, Ban H.; Ali Raheem, Maryam (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
In this work, gold nanoparticles (AuNPs) were created utilizing a plasma jet method and 0.5 gm/mol of gold salts (4H2O•HAuCl4) with varied flow diameters (0.6 mm, 0.8 mm, 1 mm, and 1.2 mm). The gas flow changes according to the system diameter (2,2.4,3.4, and 3.6 L/min, respectively). X-ray diffraction, ultraviolet, visible spectra, and FESEM were each used to investigate the nanoparticles. The XRD pattern revealed that the film's extreme peaks reflect crystallinity, with an average crystallite size of (18–26) nm and a face-centered cubic structure. The surface plasmon resonance for colloidal AuNPs produced in the UV was at 536–540 nm.A field emission scanning electron microscope (FESEM) was used to look at the morphology of the Au NPs. The round particles ranged in size from (38-65) nm. The findings of this work provide encouraging evidence for the straightforward and inexpensive production of nanomaterials with various dimensions.